Toughening of Bisphenol-A Diglycidyl Ether-based Epoxy by Modification with Hydroxyl-terminated Liquid Natural Rubber - H. L. Pham; B. T. Do; T. S. Pham; D. G. Le (ASEAN Journal on Science and Technology for Development, 2013)
Hydroxyl-terminated liquid natural rubbers (HTNRs), prepared by the Photo-Fenton reaction, were used to modify bisphenol-A diglycidyl ether-based epoxy (DGEBA). A chemical link between HTNRs and the epoxy resin was promoted employing toluene diisocyanate. The reactions between elastomers and epoxy resin were followed by FTIR. The mechanical properties of the composites were evaluated and the microstructure was investigated using scanning electronic microscopy. The results showed that the impact resistance of HTNR-modified DGEBA was superior to that of the pure epoxy resin. For the composites with HTNR, the impact resistance increased with elastomer concentration up to 2.5 parts per hundred parts of resin. Higher concentration of HTNR resulted in larger particles which gave lower impact values.